Reflective Pedagogy with Narrative and Visual Media for Enhancing Body Safety Awareness in Socioeconomically Marginalized Preschools - Ilyas, Sitti Nurhidayah; Musi, Muhammad Akil; Bachtiar, A. Muhammad Yusri; Hasmawaty; M Bakri, Tri Sugiarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Child sexual abuse continues to disproportionately affect children from socioeconomically marginalized communities, where access to body safety education remains limited. This study aims to evaluate the effectiveness of narrative and visual media animated videos, educational posters, picture storybooks, and illustrated flashcards within a reflective pedagogical framework to enhance preschoolers’ understanding of body safety. Employing a sequential mixed-methods design, the research was conducted in three under-resourced early childhood education centers, involving 116 children and six classroom teachers. Quantitative data were collected through pre- and post-tests, while qualitative insights were gathered via observations, interviews, and document analysis. Findings reveal that all four media significantly improved children’s conceptual understanding, with animated videos showing the greatest score gains and posters yielding the highest post-test averages. Qualitative analysis identified distinct pedagogical mechanisms: animated videos supported dual coding processes and emotional resonance; storybooks fostered narrative engagement but required guided mediation; posters encouraged peer interaction and contextual understanding; and flashcards, while accessible, relied heavily on teacher scaffolding and offered limited sustained engagement. Teachers played a critical role in adapting media to classroom realities, particularly in resource-limited contexts. This study underscores the pedagogical value of integrating multimodal media in early childhood body safety education, especially when mediated through reflective teaching. It highlights the need for structured curriculum inclusion, targeted teacher training, and future innovations in multimodal learning. The findings contribute to a growing call for inclusive, developmentally appropriate, and context-sensitive approaches to protective education in marginalized settings.